THE IMPLEMENTATION OF THE INTERNATIONAL COVENANT ON CIVIL AND POLITICAL RIGHT (ICCPR) AS AN INTERNATIONAL REGIME IN INDONESIA DURING THE JOKO WIDODO ERA (2014- 2019) - Nadiyah Munisah Hamelia (: 2621-0924)
This research departs from the problems in the implementation of the protection of civil and political rights in Indonesia. After ten years of the ICCPR ratification, especially during the Joko Widodo era, there some regression in the score for freedom of expression as a crucial instrument for a democratic country's human rights issue. Specifically, this study aims to analyze the International Covenant on Civil and Political Rights (ICCPR) application as an international regime in Indonesia during the Joko Widodo administration in 2014-2015. This study used a descriptive qualitative method, with data collection techniques through literature study. The data was taken from the official website of the organization as the responsible for supervising the fulfillment of human rights, such as; Kontras, ICJR, HRWG, and others, then through interview sessions with related parties, as well as several official documents, laws, reports and quarterly records. This thesis is analyzed based on the concept of human rights based on an Islamic perspective, the international regime's theory, and the concept of compliance and enforcement. This theoretical framework will help analyze how international treaties work as international regimes in binding participating States, especially Indonesia, to comply with the articles contained therein. This international regime will also later provide the formation of patterns of behavior in Indonesia and how Indonesia's compliance in implementing regulations in fulfilling its people's civil and political rights will result in two possible decreases or increases. Finally, it was found that in its implementation after ten years of ratification, the ICCPR experienced a regression in the fulfillment of its civil and political rights, several factors namely cause the obstacles to its implementation: lack of strength of norms created by the ICCPR against participating countries, the rules governing participating countries still have barriers and obstacles, which have implications for the decision making process in participating countries, Weak international coercion in taking action against mistakes Indonesia, As well as Indonesia has its logic of compliance in complying with the ICCPR as an international regime.Key Words: International Covenant on Civil and Political Right, International Regime, Indonesia